Trust And Long Term-Term Relationship dengan Brand Awareness pada Fashion Brand - Rassel Nuno Alghifari; Indri Rachmawati (UNISBA Press, 2023)
Abstract. Social media marketing is extensively conducted by many brands today to enhance brand awareness. This study aims to measure brand awarene on the Instagram platform, with a focus on the @faith.industries account in the fashion industry. Observed aspects are trust and long-term relationship. The research sample consists of 100 respondents who are followers of the account. A quantitative approach with a correlational design is employed in this study. The results of data analysis using t-test and Adjusted R Square coefficient of determination indicate a significantly strong relationship between social media marketing implemented by @faith.industries and brand awareness. These findings are further supported by interview results demonstrating high levels of brand awareness among the respondents. This research provides valuable insights into the strong connection between social media marketing and brand awareness. It confirms that aspects such as trust and long-term relationship play vital roles in building brand awareness on Instagram. The study has practical implications for marketing practitioners to enhance the effectiveness of their social media marketing strategies in building brand awareness. Utilizing high-quality content, fostering strong follower relationships, actively engaging followers, and integrating multiple marketing platforms are key factors for successful brand awareness expansion. Overall, this research contributes to a better understanding of the importance of social media marketing in building brand awareness on Instagram, particularly for the @faith.industries account in the fashion industry. Abstrak. Social media marketing gencar dilakukan oleh banyak brand saat ini untuk meningkatkan brand awareness. Penelitian ini dilakukan untuk mengukur brand awareness di platform Instagram, dengan fokus pada akun @faith.industries di industri fashion. Aspek yang diamati adalah trust and long-term relationship. Sampel penelitian terdiri dari 100 responden yang merupakan follower akun tersebut. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan pendekatan korelasional. Hasil analisis data menggunakan uji-T dan koefisien determinasi Adjuster R Square menunjukkan bahwa terdapat hubungan yang sangat kuat antara social media marketing yang diterapkan oleh @faith.industries dan brand awareness. Temuan ini juga didukung oleh hasil wawancara yang menunjukkan tingkat brand awareness yang tinggi pada responden.